Analisis sistem informasi akuntansi pembelian di Pt. Suryamustika - Romiko, Rohiima; Pardi, Pardi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the effect of purchasing components, supporting documents, document writing, and internal management on purchasing accounting information systems. This study used a quantitative method with a purposive sampling technique for 102 employees who are still actively working at PT. Suryamustika. The primary source of research data is primary data obtained from questionnaires. This study uses multiple linear regression analysis with the help of SPSS version 19. The results showed that the purchasing components, supporting documents, document writing, and internal management had an influence on the purchasing accounting information system at PT. Suryamustika. So it is important for companies to improve their accounting information system, which was previously done manually but is now digital because of increasingly advanced technology, so that each purchase order can be made faster and the data provided is also correct according to the updated data.